Quadcopter Stability Control System Using PID And Kalman Filter - Sukmaningrum, Miranti; Yulianto, Ahmad Wilda; Zakaria, Muhammad Nanak (Jurnal Jaringan Telekomunikasi, 2023)
Quadcopter is an Unmanned Aerial Vehicle (UAV) that uses 4 motors arranged crosswise as a propulsion system. The quadcopter's capabilities are supported by a main component called the flight controller or control system. The operation of this unmanned aircraft is controlled automatically through a program run from the GCS (Ground Control Station) so that the quadcopter can fly according to the desired destination. The control system is needed to maintain the balance of the quadcopter while flying and maneuvering to remain stable. PID (Proposional Integral Derivative) method as a counterweight when manoeuvring on the y-axis (pitch) and x-axis (roll) and Kalman Filter as processing the resulting sensor output. The results of this study show that setting the value for the proportional constant (Kp), integral constant (Ki) and derivative constant (Kd) determines the quadcopter can fly or maneuver well. The gain values used are Kp of 0.135, Ki of 0.135 and Kd of 0.003. However, the output generated by the gyroscope in pitch and roll still has noise caused by the vibration of the mover during flight and maneuvering. So the Kalman filter is needed to find out the value that is close to the actual output of the gyroscope.